Bimetal Seleno‐Sulfide CuNiSeS Nanosheet Catalyst for Methylene Blue Degradation in the Dark. Issue 36 (30th August 2018) - Chen, Xiaoyun; Kuo, Dong‐Hau; Wu, Zong‐Yan; Abdullah, Hairus; Zhang, Jubin; Lin, Jinguo
Abstract : In order to overcome the photocatalytic degradation reaction with a need for light excitation, the exploration of a catalyst for the organic degradation reaction without light has become one of the core challenges in catalysis and pollution control. Here we report a novel Cu NiSe S nanosheet catalyst with a hexagonal structure by a feasible preparation method. The structure and composition of Cu NiSe S were well characterized by X‐ray diffractometry and electron microscopy, and X‐ray photoelectron spectrometry, respectively. The result indicated that the best Cu NiSe S‐2 of 25 mg displayed excellent activity even in the dark to complete the degradation of 100 mL of MB solution of 10 ppm within 5 min. This catalyst also showed relatively good stability and durability during the reusability tests. The reasons for the fast MB degradation in the dark were investigated and the reaction kinetic mechanism was proposed. Abstract : A Cu‐based bimetal seleno–sulfide catalyst system with a CuS covellite structure has been developed for organic degradation that even occurs in the dark. Cu Ni SeS‐2 showed the fastest degradation of an MB solution (100 mL, 10 ppm) in 5 min, but Ni ‐free Cu Se S did not have good catalytic activity. The Cu 2+ /Cu + ratio, oxygen vacancy, and S 6+ are correlated to perform good dye degradation.